Description of a new species in the Sphaeropthalma pensylvanica species-group (Hymenoptera: Mutillidae) - Pitts, James P. (Zootaxa, 2005)
A new species, Sphaeropthalma nocticaro, is described from Oaxaca, Mexico and Petén, Guatemala. This species is placed into the S. pensylvanica species-group, with which it shares many morphological characters. This species-group is found predominately in the Southeastern USA ranging into eastern Texas, and addition of this new species greatly extends the geographic range of this group.